Ten years on the edge: Phil Fox reflects on a decade of recovery from addiction through applied theatre. (22nd August 2011) - Reynolds, James; Zontou, Zoe
Applied theatre's engagement with substance addiction and misuse remains small scale and undertheorized in the UK context. Outside Edge, led by Phil Fox, is a leading company in this field. In this interview, Phil discusses his work from its inception, tracing its development and putting it in context to reflect on a decade of practice. He addresses the challenges of using Forum Theatre as a strategy of intervention and relapse prevention and identifies some of the company's core intentions in working with those in recovery, to deny denial and to show that substance misuse is not socially compartmentalized, but rather is everyone's story.